Happy herbivore abroad : a travelogue & over 135 fat-free & low-fat vegan recipes from around the world - Nixon, Lindsay S. (Dallas, Tex. : BenBella Books ; [New York] : Distributed by Perseus Distribution, 2012)
The author shares her fat-free and low-fat vegan recipes for comfort foods and other dishes with international flavors, along with stories of her experiences living and traveling throughout the United States and around the world.
Introduction -- Soups, stews, & chilis -- Legume-based dishes -- Vegetable sides -- Stir-fries & veggie dishes -- Grain-based dishes -- Desserts & baked goods -- Pasta, noodles, & sauce -- Gravies, condiments, sauces, & toppers -- Drinks -- Spices & DIY -- USA -- Appendix.
"Recipes made with everyday ingredients"--Cover.
"Explore foods from around the world right in your own kitchen"--P. [4] of cover.
Includes index.
Keywords: Vegan cooking; Low-fat diet -- Recipes; International cooking; Cookbooks